2021
DOI: 10.3390/diabetology2010001
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Self-Management and Adaption to New Diabetes Routines: A Qualitative Study of How People with Diabetes Managed Their Illness during the COVID-19 Lockdown

Abstract: When societies went into the COVID-19 lockdown, the conditions under which people with diabetes managed their illness dramatically changed. The present study explores experiences of everyday life during the COVID-19 lockdown among people with diabetes, and how diabetes self-management routines were affected. The data consist of 20 interviews with adults with diabetes, focusing on experiences during the COVID-19 lockdown. The analysis showed that experiences of self-management during lockdown were diverse and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 52 publications
(77 reference statements)
7
42
0
Order By: Relevance
“…In comparison to evidence gathered at a similar time for the impact of the COVID-19 pandemic and lockdown restrictions on other populations with metabolic conditions, a qualitative study of adults with diabetes in Denmark reported similar challenges to selfmanagement of the condition, including access to exercise and emotional eating [46]. The findings of this study also identified anxiety relating to fear of the coronavirus and concerns about access to medication, and some participants reported that the lockdown gave them time to learn more about their condition.…”
Section: Discussionmentioning
confidence: 89%
“…In comparison to evidence gathered at a similar time for the impact of the COVID-19 pandemic and lockdown restrictions on other populations with metabolic conditions, a qualitative study of adults with diabetes in Denmark reported similar challenges to selfmanagement of the condition, including access to exercise and emotional eating [46]. The findings of this study also identified anxiety relating to fear of the coronavirus and concerns about access to medication, and some participants reported that the lockdown gave them time to learn more about their condition.…”
Section: Discussionmentioning
confidence: 89%
“…In Saudi Arabia, Sultan F. Magliah and colleagues found that the dietary habits become worse during the lockdown in 41.5% of the patients, which is not similar to this study; on the other hand, physical activity was also decreased in 67.7%, which is similar to what was found in this study (15). In Denmark, Dan Grabowski and his colleagues agreed with the Saudi's paper that lockdown has increased the consumption of unhealthy food and decreases the performance of exercise (14).…”
Section: Discussionmentioning
confidence: 98%
“…Another study demonstrated that hypoglycemic risk has increased in type 2 diabetics using insulin, anti-malarial drugs, and sulfonylureas (13). The fear of getting infected has been a challenge for performing periodic checkups (14). Most of the patients could not do HbA1c tests during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, extensive efforts have been made to find the best vaccine or treatment for COVID-19. Following hygiene principles and maintaining social distancing seem the best ways to prevent and control COVID-19 (1), which have caused changes to behavioral patterns and impeded the daily activity habits (1). Although these steps may be critical in reducing the prevalence of this disease, they will undoubtedly have long-term consequences on physical and general health (GH) (2,3).…”
Section: Introductionmentioning
confidence: 99%